2021
DOI: 10.1128/spectrum.00668-21
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Independent Detection of Poliovirus in Stool Samples by Direct RNA Extraction

Abstract: The GPLN is a global surveillance system composed of 146 laboratories in 92 countries, in each of the six World Health Organization regions. Laboratory surveillance for PV relies on virus isolation by cell culture to identify PV in stool samples from AFP cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This suggests that some of the stool samples had lost their integrity. Harrington et al found PV direct detection following RNA extraction to be significantly more sensitive than virus isolation by cell culture for PV detection in retrospective stool samples ( 21 ). In this study, the PV-positive stool suspensions were only tested with direct RNA extraction methods for PV molecular detection.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that some of the stool samples had lost their integrity. Harrington et al found PV direct detection following RNA extraction to be significantly more sensitive than virus isolation by cell culture for PV detection in retrospective stool samples ( 21 ). In this study, the PV-positive stool suspensions were only tested with direct RNA extraction methods for PV molecular detection.…”
Section: Discussionmentioning
confidence: 99%
“…Serotype-specific polioviruses were detected in the stool using a validated real-time RT-PCR assay. 18 Laboratory analysis was conducted at the US Centers for Disease Control and Prevention ( appendix p 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are two alternative direct detection technologies currently being assessed, namely (i) direct detection with intratypic differentiation (DD-ITD) and (ii) direct detection nanopore sequencing (DDNS) [ 45 , 46 ]. These methods are faster and safer alternatives compared to standard cell culture regarding containment-related risks associated with growing live viruses.…”
Section: Closing In On Poliovirus Eradicationmentioning
confidence: 99%